PERAN PEMERINTAH DESA DALAM MEMBERDAYAKAN MASYARAKAT PETANI DESA PAKONDANG KECAMATAN RUBARU KABUPATEN SUMENEP - Fathol Bari (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2021)
The purpose of this study is to determine the role of the Village Government in Empowering Farming Community and to find out how the factors that encourage and hinder the village government in empowering the community in Pakondang Village, Rubaru District, Sumenep Regency. This study uses a qualitative approach that emphasizes the human element as a research instrument. Based on the results of the research that has been done, the authors can draw the conclusion that the role of the village government in empowering farming communities can be seen from several indicators, namely: The role of the village government in fostering. The development of the life of the village community is carried out by the village head using the concept of awareness and willingness of the community itself. The role of the village government in providing services and development to the community such as in the activities of the agricultural sector, the very large contribution in agriculture is farming activities. Based on the results of interviews in the field, it shows that the government plays a very important role in providing empowerment to the community, especially in the field of agriculture, as well as the village government has provided training for the farming community on the manufacture of manure from cow dung who brought in trainers from the agricultural service with the driving factor of power as a village head who is responsible for the welfare of his village and the community is very responsive to the farmers community's creativity training on making their own fertilizer and the inhibiting factor is that many people still lack knowledge.